VD_FINDINFO Décision / 2014 / 371 vom 20. März 2014 - VD Tribunal cantonal (2014)
DÉTENTION PROVISOIRE, RISQUE DE COLLUSION | 221 al. 1 let. b CPP (CH), 222 CPP (CH), 228 CPP (CH), 393 al. 1 let. c CPP (CH)